(untitled) (Fiep Bulletin - online, 2012)
Physical Education is considered a profession in the area of scientific knowledge and discipline required of the school curriculum. In this article, the role of Physical Education professional is questioned on ethical concern with the environment and takes care of themselves and others. Aiming to verify how the EF school teachers, the public and private schools understand the need and possibilities of application of the curriculum content of education, this study used a descriptive field research with a quantitative approach. The scenario for the study was the city of Fortaleza, in the Regional II. Sixty teachers participated in the survey (30 from public schools and 30 private schools). Data collection was done from the application of a closed questionnaire containing five questions on the proposed topic and fulfilled the criteria for inclusion and exclusion, as well as the processes of ethical research. It is concluded that the teachers involved, believe it is possible through the practice of caring EF: the body and mind of his students, the next and the environment.